Effects of PID Controller on Performance of Dish Antenna Position Control for Distributed Mobile Telemedicine Nodes - Ajiboye, A. T.; Ajayi, A. R.; Ayinla, S. L. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Introduction of telemedicine into developing nation’s healthcare delivery scheme could be a solution to a number of challenges facing the scheme including acute shortage of medical personnel. Because of distribution and mobility nature of the system combined with Nigeria’s large land mass, the resulting propagation delay will be large which may lead to system poor quality of performance or instability if the system is not compensated. This study aimed at assessing the effects of introducing Proportional-Integral-Derivative (PID) controller into the control of the position of dish antenna mounted on distributed mobile telemedicine nodes within Nigeria when the link is via Nigcomsat-1R. The system closed loop composite transfer function was obtained and subjected to unit step forcing function which then yielded time domain parameters. There was reduction in the value of system time domain parameters obtained for PID controller compensated system compared to uncompensated system. Based on the value of the system time domain parameters obtained from the simulation, introduction of PID controller into this system has improved the system response significantly.